(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2017)
Genetic variability, correlation and path coefficient were studied for yield and yield component traits in twenty one diverse genotypes of pumpkin. Highest genotypic coefficient of variation was recorded for fruit length (cm), single fruit weight (kg), Brix (%) and yield per plant (kg). Heritability estimates in broad sense were higher for almost all the characters. The characters namely, fruit length, single fruit weight, yield per plant and brix% had high genotypic coefficient of variation coupled with heritability gave high genetic advance expressed as percentage of mean ranged from 76.84 to 96.06 which indicated that these characters were less influenced by environment confirming additive gene action, and therefore, selection of these characters would be more effective for yield improvement of pumpkins. Total six traits likely fruit length, fruit diameter, flesh thickness, single fruit weight and number of fruits per plant were positively and significantly associated with yield per plant. Path coefficient analysis also revealed maximum contribution of single fruit weight (0.869) to yield and this was followed by the contribution of number of fruit per plant (0.527) at genotypic level. Int. J. Agril. Res. Innov. & Tech. 7 (1): 8-13, June, 2017